2013
DOI: 10.1007/s00125-013-3009-7
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic receptor agonist administration promotes counter-regulatory responses and recovery from hypoglycaemia in rats

Abstract: Aims/hypothesis We have previously reported that local activation of β2-adrenergic receptors (B2ARs) in the ventromedial hypothalamus (VMH) enhances hypoglycaemic counter-regulation. This study examines whether peripheral delivery of a selective B2AR agonist could also promote counter-regulatory responses and thereby has potential therapeutic value to limit hypoglycaemia risk. Methods Conscious male Sprague–Dawley rats received an intra-arterial injection of the B2AR specific agonist, formoterol, or a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…In the current study, inhaled formoterol significantly decreased the amount of glucose required to keep circulating glucose at a standardized hypoglycemic level during a hyperinsulinemic clamp study in healthy control subjects and in subjects with type 1 diabetes. These findings are consistent with the established insulin antagonistic effects of formoterol in humans ( 25 ) as well as rodent data showing that peripheral administration of formoterol mainly acts to directly increase hepatic glucose production with no significant effect on counterregulatory hormones ( 22 ). These results imply that the metabolic effects of inhaled formoterol are most likely due to a direct effect of formoterol on β-2 receptors in the peripheral tissues (i.e., hepatic glucose production and/or insulin-stimulated peripheral glucose uptake).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, inhaled formoterol significantly decreased the amount of glucose required to keep circulating glucose at a standardized hypoglycemic level during a hyperinsulinemic clamp study in healthy control subjects and in subjects with type 1 diabetes. These findings are consistent with the established insulin antagonistic effects of formoterol in humans ( 25 ) as well as rodent data showing that peripheral administration of formoterol mainly acts to directly increase hepatic glucose production with no significant effect on counterregulatory hormones ( 22 ). These results imply that the metabolic effects of inhaled formoterol are most likely due to a direct effect of formoterol on β-2 receptors in the peripheral tissues (i.e., hepatic glucose production and/or insulin-stimulated peripheral glucose uptake).…”
Section: Discussionsupporting
confidence: 90%
“…In summary, our results from this pilot study suggest that specific β-2 agonists delivered via inhalation may prove useful during intensive insulin therapy in patients with type 1 diabetes who have hypoglycemia-associated autonomic failure and thus are at high risk for hypoglycemia. Its effects occur rapidly and appear to be a direct effect of formoterol on peripheral glucose metabolism, particularly in the liver ( 22 ), because counterregulatory hormone responses were not significantly altered in subjects with and without diabetes. Although, as our data suggest, formoterol acts to directly offset the effects of insulin and most likely can cause mild hyperglycemia (similar to the studies using terbutaline for hypoglycemia [ 18 ]), we believe that due to the limited options for prevention of hypoglycemia, a more specific β-agonist might benefit a particular group of patients unable to generate a counterregulatory hormone response, resulting in a history of severe and frequent hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of β-arrestin-2 also prevented the cAMP-binding protein Epac1-induced histone deacetylase 4 (HDAC4) nuclear export [11]. β2-adrenergic receptor agonists may possibly exert multiple effects including a direct-effect on liver β2-adrenergic receptors and could promote recovery from insulin-induced hypoglycemia [12].…”
Section: Introductionmentioning
confidence: 99%
“…The sympathetic-adrenal system is rapidly activated in order to increase blood glucose levels in hypoglycemia and the α 2A- receptor is an important regulator of glycemia which, when activated, inhibits the release of insulin by pancreatic β cells ( 25 ). It has been recently suggested that activation of peripheral β 2 -adrenoceptors (possibly in the liver) and of the ventromedial region of the hypothalamus also occurs in rats with insulin-induced hypoglycemia as a counter-regulatory response for the recovery of glycemic levels ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%